Image Inpainting Using Robust Exemplar-based Technique - Gaonkar, Sayali R; Hire, Priyanka D; Pimple, Prachiti S; Kotwal, Yogita R; Ahire, B.A (International Journal of Computer Sciences and Engineering, 2014)
Image in-painting is the art of restoring lost and selected parts of an image based on the background information in such a way so that the change is not observed by the observer. Image in-painting techniques is used in many fields like heritage preservation, films etc. In this paper, we are using exemplar based inpainting algorithm, this approach propagates the image information from the known region into the missing region at patch level. We first note that exemplar-based texture synthesis contains the essential process required to replicate both texture and structure; the success of structure propagation, however, is highly dependent on the order in which the filling proceeds. The existing algorithms are combined to improve the efficiency for finding the line association in selected region. Main focus is on data term and confidence term to find association in selected region which is to be inpainted. The region filling is done from that line associated to other section in selected region.